2006
DOI: 10.1038/ncb1481
|View full text |Cite
|
Sign up to set email alerts
|

Sall4 modulates embryonic stem cell pluripotency and early embryonic development by the transcriptional regulation of Pou5f1

Abstract: Embryonic stem (ES) cells are pluripotent cells that can self-renew or differentiate into many cell types. A unique network of transcription factors and signalling molecules are essential for maintaining this capability. Here, we report that a spalt family member, Sall4, is required for the pluripotency of ES cells. Similarly to Oct4, a reduction in Sall4 levels in mouse ES cells results in respecification, under the appropriate culture conditions, of ES cells to the trophoblast lineage. Sall4 regulates transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
440
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 508 publications
(455 citation statements)
references
References 26 publications
13
440
0
2
Order By: Relevance
“…[20][21][22][23] SALL4 forms a regulatory circuit with OCT4, NANOG, and SOX2 to maintain embryonic stem cell pluripotency and self-renewal. [24][25][26][27][28][29] In this self-stabilizing network, SALL4 regulates OCT4 transcription, suggesting acting upstream of OCT4. 28 In this study we have shown that SALL4 has a broader expression pattern than OCT4 in primary germ cell tumors of the CNS.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[20][21][22][23] SALL4 forms a regulatory circuit with OCT4, NANOG, and SOX2 to maintain embryonic stem cell pluripotency and self-renewal. [24][25][26][27][28][29] In this self-stabilizing network, SALL4 regulates OCT4 transcription, suggesting acting upstream of OCT4. 28 In this study we have shown that SALL4 has a broader expression pattern than OCT4 in primary germ cell tumors of the CNS.…”
Section: Discussionmentioning
confidence: 96%
“…[24][25][26][27][28][29] In this self-stabilizing network, SALL4 regulates OCT4 transcription, suggesting acting upstream of OCT4. 28 In this study we have shown that SALL4 has a broader expression pattern than OCT4 in primary germ cell tumors of the CNS. OCT4 only labeled germinomas and embryonal carcinomas, whereas SALL4 not only stained germinomas and embryonal carcinomas but also all yolk sac tumors and some teratomas (9/14) and choriocarcinomas (2/3).…”
Section: Discussionmentioning
confidence: 96%
“…Using gene expression profiling approaches, we recently identified the activation of transcription factor Sal-like protein 4transcription factor which plays a fundamental role in the maintenance of embryonic stem cells, possibly through interaction with octamer-binding transcription factor 4, sex determining region Y-box 2, and Nanog [19][20][21][22][23][24]. It has been reported by three independent groups that SALL4 is a biomarker of HCCs with stem-like gene expression signatures and a poor prognosis [18,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Recent studies have shown that the maintenance of pluripotency and self-renewal of embryonic stem cells is controlled by a regulatory circuit that includes not only OCT4, NANOG, and SOX2 but also SALL4. 26,29,30 In this network, SALL4 appears to control transcription of OCT4. 29 The relation between SALL4 and OCT4, NANOG, and SOX2 suggests that SALL4 might be also a marker for metastatic germ cell tumors.…”
mentioning
confidence: 99%
“…26,29,30 In this network, SALL4 appears to control transcription of OCT4. 29 The relation between SALL4 and OCT4, NANOG, and SOX2 suggests that SALL4 might be also a marker for metastatic germ cell tumors. The goal of the current study was to investigate the potential utility of SALL4 as a diagnostic marker in a large series of 90 metastatic germ cell tumors from the testis (n ¼ 73), ovary (n ¼ 13), and extragonadal sites (n ¼ 4).…”
mentioning
confidence: 99%